(untitled) (Research, Society and Development, 2021)
The objective of this paper is to address the challenges and the importance of pharmaceutical assistance in disseminating information, as well as analyzing the influence of the media on the increase in drug consumption during the COVID-19 pandemic. The present study is a literature review, where searches were carried out through the databases SCIELO (Scientific Electronic Library Online), LILACS (Latin American Health Science Literature), Academic Google, World Health Organization, Pan- American Health, and Federal Council of Pharmacy. On March 11, 2020, WHO formally declared the existence of a pandemic caused by a new coronavirus, SARS-CoV-2; due to the epic and frightening moment, several beliefs and unfounded information emerged in miraculous medicines that would prevent and even cure COVID-19, in some states the so-called “COVID-19 kit” were distributed. This theme is in the context of public health, on a global scale, especially with regard to the rational use of medicines, involving consumer safety and off-label prescriptions. The increase in off-label drug consumption during the pandemic is notorious. WHO and Anvisa need to be aware that potential negative effects of a drug without scientific evidence for a given disease, can bring serious future risks.